Advances in superparamagnetic iron oxide nanoparticles modified with branched polyethyleneimine for multimodal imaging - Shen, Qiaoling; Yu, Chunjing (Frontiers in Bioengineering and Biotechnology, 2024)
Multimodal imaging are approaches which combines multiple imaging techniques to obtain multi-aspect information of a target through different imaging modalities, thereby greatly improve the accuracy and comprehensiveness of imaging. Superparamagnetic iron oxide nanoparticles (SPIONs) modified with branched polyethyleneimine (BPEI) have revealed good biocompatibility and stability, high drug loading capacity and nucleic acid transfection efficiency. SPIONs have been developed as functionalized platforms which can be further modified to enhance their functionalities. Those further modifications facilitate the application of SPIONs in multimodal imaging. In this review, we discuss the methods, advantages, applications, and prospects of BPEI-modified SPIONs in multimodal imaging.